If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(2x + -2) = 16 Reorder the terms: 7(-2 + 2x) = 16 (-2 * 7 + 2x * 7) = 16 (-14 + 14x) = 16 Solving -14 + 14x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + 14x = 16 + 14 Combine like terms: -14 + 14 = 0 0 + 14x = 16 + 14 14x = 16 + 14 Combine like terms: 16 + 14 = 30 14x = 30 Divide each side by '14'. x = 2.142857143 Simplifying x = 2.142857143
| 7+6m=22+m | | y=x(-0.0125x+0.5) | | 2/5x-18=-14 | | 3y-8=y+4 | | 13u-11u+5=19 | | 4k+3=2k+17 | | 2(y-2)+y=5 | | 12=5x+5x+2 | | z-2z+-4=3 | | -6x^3-24=-6x^2-24x | | -n^2-6n-9=0 | | 5(x+7)-8x+12= | | 5a=a+20 | | 3(6m+1)=20 | | 4t=2t+14 | | -5y+14y=-18 | | 4x^(-2/3)=16 | | 11x=5-x | | -4(v-1)=-2v-16 | | 4x^-2/3=16 | | 2.50x+9.75y=36.50 | | ax^2=4x+7 | | 12y+11=49 | | 45x^2+25x^5+20x^2=0 | | 9/33=12/x | | 12s-5s=14 | | -4y+2=-5y-3 | | -3n(2n+-5)=0 | | 8x-2=4+6x | | -4r^2+7r-9=0 | | x=-16x^2+16x+192 | | 11x+13y+17z=132 |